The Acetylation-based synthesis of 3,3',4',5,5',7-hexaacetate myricetin and evaluation of its anti-inflammatory activities in lipopolysaccharideinduced RAW264.7 mouse macrophage cells - Lama, Kristina; Hong, Hyehyun; Park, Tae-Jin; Park, Jin-Soo; Chi, Won-Jae; Kim, Seung-Young (Korean Society for Applied Biological Chemistry, 2023)
Recent studies have highlighted the link between diseases and inflammation across our lifespan. Our sedentary lifestyle, high-calorie diet, chronic stress, chronic infections, and exposure to pollutants and xenobiotics, collectively intensify the course and recurrence of infections and inflammation in our bodies, promoting the prevalence of chronic diseases and aging. Given such phenomena and considering additional factors such as the frequency of prescription, and easy access to over-the-counter drugs, the need for anti-inflammatory therapeutics is everincreasing. However, the readily available anti-inflammatory treatment option comes with a greater risk of side effects or high cost (biologics). Therefore in this growing competition of discovering and developing new potent anti-inflammatory drugs, we focused on utilizing the established knowledge of traditional medicine to find lead compounds. Since lead optimization is an indispensable step toward drug development, we applied this concept for the production of potent anti-inflammatory compounds achieved by structural modification of flavonoids. The derivative obtained through acetylation of myricetin, 3,3',4',5,5',7-hexaacetate myricetin, showed a greater inhibitory effect in the production of pro-inflammatory mediators such as nitric oxide, Prostaglandin E